Ações de professores de escolas regulares com crianças com transtorno do espectro autista - Gallo, Giulia Calefi (2016)
The main characteristics of Autistic Spectrum Disorder (ASD) are deficits in communication, socio-emotional reciprocity, non-verbal communication and development. In addition, they present restricted and repetitive patterns of behavior, interests or activities, insistence on the same subject, ritualized patterns of verbal and nonverbal behavior, fixed interest with unusual focus or intensity. Although people with ASD are considered persons with disabilities (Act No. 12764) being subject to the same laws and possess the rights to be included in regular education, it is still a very incipient practice in Brazil. Considering the ASD characteristics and their impact on interactions in the classroom and the unpreparedness of the professionals dealing with ASD child behavior characteristics in the classroom, are found in the literature the Evidence-Based Practices, identified as effective in teaching children with ASD. However, due to the lack of studies that demonstrate the use of these Evidence-Based Practices in Brazil, the aim of this study was to evaluate the practices used by regular rooms teachers in interventions with ASD children. Five teachers from two regular schools with ASD students participated of the research. Six interaction observations sessions of 40 minutes each in average were made with each of the teachers and children with ASD. Every teacher's action directed at children with ASD was dictated in low voice to the recorder. Subsequently, the speeches were transcribed and those transcriptions sought to identify the actions used by teachers based on a protocol. These observations were analyzed by the rate of responses to the applied practices. The results showed that the main behaviors issued by teachers in relation to children with ASD were general instruction to the room; direct question to the student (physically distant); direct question to the student (physically close); direct instruction - verbal cue (physically distant); direct instruction - verbal cue (physically close); Teacher provides physical assistance; Teacher provides physical tip (involves sign tip and tip by model); Teacher ignores the child's behavior; Teacher physically approaching the child; "Containment" physical (safe in the arm / hand / leg) for the child does not leave the room / wheel / activity. Only one of five teachers offered educational activities tailored to the student with ASD. Teachers use the same actions regardless of the needs of the student. Consequently, it follows the need to modify the perspectives before these children, making possible changes in the actions and procedures used with these children in the classroom to promote learning.